Fishery Potential of Red Lionfish Pterois volitans Linnaeus from Cuddalore Coast South East Coast of India - Subramaniyan, A (International Journal of Pharmaceutical & Biological Archive, 2013)
Fishery Potential of Red Lionfish Pterois volitans Linnaeus from Cuddalore Coast South East Coast of India